1999
DOI: 10.1159/000053604
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in Nasal Reactivity in Children with Allergic Rhinitis: Correlation with the Activity of Eosinophils and Basophilic Cells

Abstract: Background: In allergic rhinitis, the major symptoms of runny nose, sneezing, and stuffy nose tend to become worse upon waking up in the morning, and yet the mechanisms underlying this phenomenon are poorly understood. We investigated whether the worsening of allergic rhinitis in the morning is associated with changes in the activity of inflammatory cells. Methods: Nasal reactivity to methacholine was assessed twice in 8 children with allergic rhinitis and 8 healthy control subjects at 6.00 a.m. and 3.00 p.m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
1
31
0
1
Order By: Relevance
“…36,37 Allergic rhinitis-related inflammatory mediators also exhibit a circadian pattern, with levels peaking in early morning. 38 In addition, sympathetic tone decreases at night, resulting in a relative parasympathetic excess, which is associated with nasal congestion and reduced bronchial dilation. 39 Several mediators involved in the allergic response also have been implicated in the pathophysiology of sleep disruption.…”
Section: Mechanisms Of Nasal Congestion: Impact On Sleep Quality and mentioning
confidence: 99%
“…36,37 Allergic rhinitis-related inflammatory mediators also exhibit a circadian pattern, with levels peaking in early morning. 38 In addition, sympathetic tone decreases at night, resulting in a relative parasympathetic excess, which is associated with nasal congestion and reduced bronchial dilation. 39 Several mediators involved in the allergic response also have been implicated in the pathophysiology of sleep disruption.…”
Section: Mechanisms Of Nasal Congestion: Impact On Sleep Quality and mentioning
confidence: 99%
“…Mediators from eosinophils, particularly eosinophil cationic protein, play a pivotal role in the pathogenesis of allergic rhinitis and are under intensive investigation [51, 52, 53, 54]. The levels of inflammatory products of eosinophils and basophilic cells (ECP, histamine and tryptase) in nasal secretions showed a direct association with the circadian variation in nasal reactivity to methacholine and symptoms of allergic rhinitis [55]. Our data showed that the number of eosinophils from nasal mucosa in patients with HDM-sensitive allergic rhinitis was correlated with levels of ICAM-1 expression on nasal epithelial cells, a stuffy nose, and the number of neutrophils from nasal mucosa, whereas ICAM-1 expression on the nasal mucosal epithelial cells did not correlate with any parameters except the number of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…This daily rhythm in hypersensitivity to allergens contributes to the daily rhythms observed in AR (Nakamura et al 2011;Nakamura et al 2016). For example in children exposed to an allergic challenge at 6 am, more nasal secretions are produced than when exposed at 3 pm (Aoyagi et al 1999). Furthermore, the commonest allergen for patients suffering from AR is house dust mite.…”
Section: Allergic Rhinitismentioning
confidence: 99%